Role of serum tumour necrosis factor alpha and its soluble receptors in predicting acute renal allograft rejection - Said, Seham Ahmed; Mahmoud, Mostafa Ayman; El-Fettouh, Ibrahim Abu (African Journal of Nephrology, 2016)
<p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Tumour necosis factor alpha (TNF-?) is known to be involved in pathogenesis of acute renal allograft rejection. However, measurement of cytokine serum levels alone are not a reliable index of acute rejection episodes. TNF-?induces the release of soluble receptors (TNF-SR55 and TNF-SR75) that have an inhibitory activity and catabolized by the kidney. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Twenty nine transplant recepients were studied and compared to ten healthy controls. TNF-?, TNF-SR55 and TNF-SR75 were measured before and after renal transplantation. The mean pre-transplantation values were 26.3 9.7 pg/ml, 28.2 8.3 and 42.5 11.1 ng/ml respectively. According to post-transplant course patients were divided into 3 groups. Group I (stable transplant group: no= 17): The mean level of TNF-?value was 7.5 4.6 pg/ml, TNF-SR55 6.4 4.7 and TNF-SR75 12.5 8 ng/ml (p NS). Group II (acute allograft rejection group: no = 8): The mean values were 37.2 16.2 pg/ml, 16.9 9.6 and 30.9 13.4 ng/ml respectively (p< 0.05). Group III cyclosporine (CS) nephrotoxicity group: no= 4): The mean level of TNF-? was 9.9 2.1 pg/ml with a highly significant increase in its receptor values (9.4 1.0 & 21.2 6.8 ng/ml; vs 5.5 1.2 & 12.4 4.8 ng/ml respectively (P< 0.01). To improve the predictive value of this cytokine and its receptors,we calculated the ratios of TNF-a to both receptors (SR55-SR75). During acute rejection episode, the ratio values tocontrol were 2.4 0.6 vs 1.4 0.7 and 1.3 0.5 vs 0.7 0.4 respectively (P< 0.01). However, these ratios did not change significantly from control group during CS nephrotoxicity 1.5 0.5 vs 2.0 0.7 and 0.5 0.3 vs 0.9 0.2 respectively (p>0.05). Thus, TNF-? and its soluble receptor levels might be of diagnostic value in renal allograft rejecion. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">In conclusion: 1) TNF-? and its soluble receptors are highly increased during hemodialysis. 2) There is no significant difference between healthy controls and patients with stable grafts. 3)There is highly significant increase of TNF-? and its receptors during acute rejection episodes and the day (R-2) prerejection in contrast to internal controls. 4) There is insignificant decrease of TNF-? during CS nephrotoxicity with highly significant increase of TNF-SR55, TNF-SR75 when compared to internal controls. 5) The ratios of TNF-?to SR55 & SR75 showed highly significant increase during acute rejection episodes and insignificant decrease during CS nephrotoxicity when compared to internal controls.